(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women entrepreneurship was a dismissed area amid the past, yet with the spread of education and awareness among the women the photo has been changed and the women have risen as the present most critical and moving entrepreneurs. It is said that family is a chariot with wheels which are driven by both the male and female individuals from the family. In the event that one of the wheels is lingering behind, the chariot i.e. the family won’t have the capacity to develop and create. In a similar way when we talk about a country, the Women entrepreneurship assumes a prevailing part in the monetary advancement and makes critical commitments to the financial development of the country. The improvement of the country would be moderate if the women entrepreneurship is overlooked and ceased to join the standard of beneficial exercises. This paper unfurls the criticalness of women entrepreneurship and furthermore centers the part of women entrepreneurs in the Indian economy and furthermore their commitments to the monetary advancement. Different roader targets like development with value can be accomplished by empowering the advancement of women entrepreneurship. There is need of trim and forming the women entrepreneurship with the entrepreneurial traits and skills. In this research paper we have taken Percentage and Garrett’s Ranking Technique for analysis